Efficiency of the D-chiro-inositol for the polycystic ovary syndrome - Т. Л. Архипкина; Л. П. Любимова (Publishing House TRILIST, 2019)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder that develops in 10-15% of reproductive aged women. Over the past two decades, the inositol effectiveness in normalizing the clinical and hormonal disorders associated with PCOS has been actively studied. Inositol and its stereoisomers are classified as insulin sensitizers and act as a second conductor for insulin transmission routes. Myo-inositol and D-chiro-inositol are two of the nine existing stereoisomers the most studied currently, which play an important role in the PCOS physiology and treatment. The aim of the study was to study the Protalis effectiveness in patients with PCOS. 40 women with PCOS (mean age 24.4 ± 0.8 years) who were resistant to previous treatment with clomiphene citrate were examined. Protalis was administered for three months, after the end of the drug intake clomiphene citrate was used according to the standard regimen to restore fertility. The levels of luteinizing hormone, follicle-stimulating hormone, sex hormone binding globulin, total testosterone, antiMullerian hormone, homocysteine, folic acid were determined, and free androgen index was calculated. Fasting insulin was tested in serum and 120 minutes after the glucose load, the HOMA-IR was calculated, and lipid metabolism parameters were studied. Monotherapy with Protalis normalized the menstrual cycle in 52.5%, restore ovulation in 40%, contributed to the pregnancy in 7.5% patients with PCOS, in combination with clomiphene citrate in 27.5% women previously resistant to clomiphene. No changes in body mass index, waist circumference/hip circumference or hirsutism were found. A decrease in hyperandrogenism due to a testosterone decrease and an sex hormone binding globulin increase was found, the carbohydrate, lipid metabolism, and folate status improved. Protalis monotherapy can be recommended for patients with PCOS as a preliminary preparation, potentiating the clomiphene citrate effects, on the background insulin resistance. It is advisable to consider the Protalis use in combination with drugs for standard treatment of PCOS.